Dormancy-breaking of foxtail millet seeds (Setaria italica L. Beauv.) using ultra-fine bubble water and plasma technology - Putri A. DHIFA; Mohamad R. SUHARTANTO; Sintho W. ARDIE; Yohanes A. PURWANTO (Notulae Scientia Biologicae)
Seed dormancy is one of the key challenges in the development of foxtail millet (Setaria italica L. Beauv.). This study explored the use of ultra-fine bubbles water (UFBW) and plasma-activated water (PAW) to break seed dormancy in foxtail millet by first identifying the causes of dormancy and then evaluating the effectiveness of these innovative treatments. Two experiments were conducted using the ICERI-6 and Botok-10 genotypes: the first involved storing seeds at either ambient temperature or 20 °C for up to six weeks to observe dormancy patterns, while the second tested various dormancy-breaking treatments, including a control, KNO₃ (0.1%), UFBW at two dissolved oxygen concentrations (8 and 20 mg·L⁻¹), and PAW with two plasma exposure times (10 and 20 minutes, each containing 0.1 mg·L⁻¹ ozone). Results showed that foxtail millet seeds exhibit physiological dormancy, as indicated by an increasing GA:ABA ratio during storage. Dormancy was naturally broken at ambient temperature by the fifth week for ICERI-6 and the sixth week for Botok-10, whereas storage at 20 °C induced secondary dormancy. Both UFB and PAW treatments significantly increased germination rates and speed, reduced dormancy intensity, and shortened the after-ripening period, down to two weeks for ICERI-6 and three weeks for Botok-10, demonstrating that these technologies are effective, chemical-free alternatives for breaking seed dormancy and improving germination in foxtail millet.